Pembinaan Antusiasme Beribadah dan Sikap Komitmen Kebangsaan pada Santri di Pondok Pesantren Mahasiswa Nurul Huda Blotongan Kota Salatiga Tahun 2023 - Agung Dermawan, Yudi; Aji Nugroho, Muhammad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to find out: (1) Fostering enthusiasm for worship for students at the Nurul Huda Blotongan Student Islamic Boarding School, Salatiga City in 2023 (2) Fostering an attitude of national commitment to students at the Nurul Huda Blotongan Student Islamic Boarding School, Salatiga City in 2023 (3) The impact of coaching enthusiasm for worship and an attitude of national commitment to students at the Nurul Huda Blotongan Student Islamic Boarding School, Salatiga City in 2023. This research uses a qualitative descriptive research type with a phenomenological approach. Data collection techniques carried out by observation, interviews and documentation. The informants in this study were caregivers, asatidz, administrators and students at the Nurul Huda Blotongan Islamic Boarding School, Salatiga City. Data analysis is used through activities, namely: data reduction, data presentation and drawing conclusions. In checking the validity of the data, researchers used source triangulation and technical triangulation. The results showed that: (1) Fostering enthusiasm for worship in students was applied by studying the yellow book, habituation (ta'widiyah), motivation and exemplary (uswah). (2) Fostering the attitude of national commitment to students through student activity units, deliberations and contextualization. (3) The impact of fostering enthusiasm for worship in students is that students can carry out worship without having to be forced, students can get up at night to carry out worship, it becomes a good habit for students, students get peace of mind and students can establish friendly relations with the community. (4) The impact of fostering an attitude of national commitment to students is that students become patriotic, peace-loving, united, tolerant, humble and moderate.